PHYSICAL ACTIVITY AND NUTRITION AS A MAJOR FACTOR IN CONTROL OF BODY COMPOSITION (Fiep Bulletin - online, 2012)
Physical activity and nutrition have been addressed in the media with relevant importance because they are directly associated with health. The objective of this research is to clarify important factors related to physical activity and nutrition requirements as prevalent in the control of body composition. This study was based on a quantitative and qualitative research, through the statistical method in order to verify the relationship between body composition and physical activity level and diet quality. Data from the field study were collected in Regional Public Hospital in the municipality of Altamira Trans / PA. We found a high level of physical inactivity as between the hospital staff, as only 35.07% practice regular physical activity, while 64.93% do not. We found evidence from the survey data field with the literature, because a sedentary lifestyle leads many individuals to acquire an outside body composition of ideal standards, and exercise combined with good nutrition directly influence the body composition of an individual.
Keywords: Physical Activity; Nutrition and Body Composition.